2018
DOI: 10.1515/cclm-2017-0609
|View full text |Cite
|
Sign up to set email alerts
|

No additional value of conventional and high-sensitivity cardiac troponin over clinical scoring systems in the differential diagnosis of type 1 vs. type 2 myocardial infarction

Abstract: The diagnostic information provided by serial measurements of conventional or hs-cTnT is not better than that yielded by a simple clinical scoring model. Absolute changes are more informative than relative troponin changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…A total of 40 studies were included for analysis13–52 and their characteristics are summarised in online supplemental table S3. They comprised a total of 127 620 participants of whom 98 930 participants (77.5%) were classified as T1MI and 13 803 (10.8%) as T2MI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 40 studies were included for analysis13–52 and their characteristics are summarised in online supplemental table S3. They comprised a total of 127 620 participants of whom 98 930 participants (77.5%) were classified as T1MI and 13 803 (10.8%) as T2MI.…”
Section: Resultsmentioning
confidence: 99%
“…The 2007 definition1 was used in 7 (17.5%) studies,15 16 27 29 43 44 52 the 2012 definition2 in 25 (62.5%) studies,13 17 19–21 23–26 30–35 37 39 40 42 45–48 50 51 and the 2018 definition3 in 8 (20%) studies 14 18 22 28 36 38 41 49. Of the 40 studies, 17 (42.5%) were prospective15 16 18 19 22 29 33 34 36 37 43–45 47 48 50 51and 23 (57.5%) were retrospective 13 14 17 20 21 23–28 30–32 35 38–42 46 49 52…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With a cut-off of 17.5 × 10 3 , we found that the CRP/troponin ratio had a specificity of 90% for T2MI versus T1MI, which could help the choice of not performing immediate PCI. Troponin has already been highlighted as a useful biomarker for the distinction between T1MI and T2MI in patients presenting to the ED, especially when considering the delta of concentrations at admission and after 4 h [24,25], but when considered alone, poorly discriminates T2MI from TIMI [26]. Nowak et al assessed the predictive value of N-terminal-pro brain natriuretic peptide (NT-Pro BNP)/troponin ratio for the differentiation of 25 T1MI cases from 18 T2MI cases in the ED [27].…”
Section: Differentiation Between T1mi and T2mi In Cad Patientsmentioning
confidence: 99%